(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The business case for Philtransure’s Logistic 1 (TNVS) Transport Network Vehicle System outlines the project’s benefits, recommendations, reasoning, and how it will address current business challenges. It also details project objectives, performance metrics, assumptions, constraints, and alternative options. Logistics are critical to a successful supply chain as they aid companies involved in product manufacturing, warehousing, and delivery to increase sales and profitability. Even a small error in logistics can cause production delays and financial losses. The approach used is agile methodology, which is designed for rapid development. The suggested system development process includes Requirement Analysis, Design Document, Prototype, Iteration, Demo and Feedback, fault detection and resolution, and Production and Technical Support. This methodology is widely used and highly recommended for guiding the development team towards their desired output system. To facilitate their communication, users can create and link with other departments for their transactions and information needs. Users need to have transparency when interacting with other departments.